Prof. Armando Mansilha - Mansilha, Armando (Gazeta Médica, 2017)
Professor of Angiology and Vascular Surgery of the Faculty of Medicine of University of Porto Head of the Department of Angiology and Vascular Surgery at Hospital CUF Porto Secretary General of the Section and Board of Vascular Surgery of the European Union of Medical Specialists (UEMS) ESVS 2015 LOC Chairman President Elect of the European Venous Forum Honorary Member of the Vascular Society of Great Britain and Ireland